IP-based nanoBTS pilot project - Oducayen, Charlie R. (Animo Repository, 2022)
The practicum program has offered the proponent an opportunity to be part of the innovative trend in technology related to the future mobile services. Skills and knowledge were enhanced not only on the field of Mobile Switching Technology but as well as on the Internet Protocol (IP) technology. There is an alternative cost effective solution for mobile operators in the expansion of their network. That broadband packet data otherwise known as “IP” connectivity will become a near ubiquitous utility, comparable with water and electricity in its reach and influence